Vibration Analysis and Design of the Oilcan Spraying Robot - Zhang Hong; Chen Lei; Ding Shiyong (Jixie chuandong)
According to the actual situation of the construction site and the problems of the oilcan spraying robot,such as spraying inefficiently,can’t adapt to the size of each oilcan,can’t meet the use of sand blasting and spray painting,an oilcan modular smart spraying robot is designed. The overall structure and the key components of the robot are described. The designed robot can realize some functions,like automatic lifting,rotating,the movement of the spraying car,the adjustment of spray gun angle,visual feedback,etc by the detection of machine vision and the intelligent judgment. This robot can adapt to the size of each oilcan by adjusting the number of boom sections and the fixed column sections. It can be used both for sand blasting and spray painting. At last,the modeling and analysis of booms and the fixed column as the key structure of the spraying robot are carried out. The result shows that the key structure will not resonate in the work.